Peningkatan pengetahuan untuk pencegahan stunting melalui sosialisasi dan demo pembuatan makanan balita berbahan dasar protein hewani bagi kelompok istri peternak sapi pedaging rumahan di Desa Lando, Lombok Timur, Nusa Tenggara Barat [Increasing knowledge for stunting prevention through socialization and demonstration for creating animal protein-based toddler food for a group of wives of home-based beef cattle farmers in Lando Village, East Lombok, West Nusa Tenggara] - Qurnianingsih, Ema Ema; Rusyda, Aqila sabila; Hamzah, Arshq Mirza; Rachmawati, Kadek; Humairah, Ira Ira; Lukitasari, Lina; Khaerunnisa, St; Wungu, Citrawati Dyah Kencono; Ummah, Fithriyah Cholifatul Ummah; Kholik, Kholik; Riwu, Katty Hendriana Priscilia; Pradana, Munawer; Yansri, Alifianita Anake; Hidayat, Muhammad; Prabowo, Gwenny Ichsan (Universitas Syiah Kuala, 2024)
Stunting is a condition of failure to thrive in children under five (toddlers) which can hinder the child's physical and mental development. Data from the 2023 Indonesian Health Survey (SKI) shows that the number of stunted toddlers in West Nusa Tenggara (NTB) Province is still quite high, namely 24.6%. Stunting cannot be cured but can be prevented. One of the prevention efforts is to increase the knowledge of mothers or prospective mothers regarding stunting and preventing it by providing food with high nutrition. This Community Service Activity (PKM) was carried out with the aim of educating mothers and wives of home-based beef cattle farmers in Lando Village, East Lombok, NTB about preventing stunting by providing highly nutritious supplementary food (PMT) and stunting detection. The methods used were socialization and demonstration of making toddler food. The results of this PKM activity were that there was a significant increase in participants' knowledge regarding the material being socialized (p0.0001). The conclusion that can be drawn is that There had been an increase in knowledge among PKM participants regarding stunting and preventing stunting through providing food with high protein content.